Novel Powdered Anti-adhesion Material: Preventing Postoperative Intra-abdominal Adhesions in a Rat Model - Takagi, Katsunori (Ivyspring International Publisher, 2013)
Background: Although laparoscopic surgery has decreased postoperative adhesions, complications induced by adhesions are still of great concern. The aim of this study was to investigate the anti-adhesive effects of a novel powdered anti-adhesion material that can be applied during laparoscopic surgery in comparison with other anti-adhesion materials. Methods:Our novel powdered anti-adhesion material is composed of aldehyde dextran and ε-poly(L-lysine). In 40 male rats, a 2.5×2.0-cm abdominal wall resection and cecum abrasion were performed. The rats were randomized into four groups based on the anti-adhesion treatments: normal saline; Seprafilm(®); Interceed(®); and novel powdered anti-adhesion material. The animals were euthanized on days 7 and 28 to evaluate the adhesion severity, area of adhesion formation, gross appearance, and pathological changes. Results: The adhesion severities on both days 7 and 28 were significantly lower for all anti-adhesion material groups compared with the normal saline group (p<0.05). Pathologically, all groups showed inflammatory cell infiltration on day 7 and complete regeneration of the peritoneum on day 28. Conclusions:Our novel powdered anti-adhesion material was found to be effective for reducing postoperative intra-abdominal adhesions and showed equivalent efficacy to commercial anti-adhesion materials.